The Effect of Breast Care on Breast Milk Production in Postpartum Women at Mokopido Tolitoli Hospital: Pengaruh Perawatan Payudara terhadap Produksi ASI pada Ibu Nifas di RSUD Mokopido Tolitoli - Sriwanti Ambabunga; Azwar Azwar; Hasni Hasni; Mutiara Mutiara (Salando Health Journal, 2025)
The postpartum period is a critical phase in a mother's recovery following childbirth, during which breast milk (ASI) production plays a vital role in successful breastfeeding. Breast care is a non-pharmacological intervention believed to enhance milk production by stimulating the hormone oxytocin. This study aims to evaluate the effectiveness of breast care on breast milk volume among postpartum mothers at Mokopido Regional General Hospital in Tolitoli. The research employed a quasi-experimental design with a posttest-only control group approach, involving 60 respondents divided into two groups: an intervention group (receiving breast massage) and a control group (without breast massage). Breast milk production was measured on the 3rd, 4th, and 5th postpartum days using an electric breast pump and a precision digital scale. The results showed a significant increase in milk production in the intervention group compared to the control group, with the average volume on the 5th day reaching 185 ml in the intervention group and 115 ml in the control group (p < 0.05). These findings indicate that breast care is effective in enhancing breast milk production. It is recommended that this technique be integrated into standard postpartum care services to support the success of exclusive breastfeeding